2015
DOI: 10.12720/joams.3.1.44-49
|View full text |Cite
|
Sign up to set email alerts
|

Antecedents and Consequences of Union Participation: A Review

Abstract: Labour unions unquestionably rely on member participation for their survival and ability to meet members' needs. However, there has been relative lack of participation by the membership in union activities. The present study is done with motive of identifying and developing a theoretical model depicting relationship between antecedents and consequence(s) of union participation, using systematic literature review as proposed by Tranfield, Denyer and Smart. While Demographic Variables, Union Commitment, Union In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(22 citation statements)
references
References 45 publications
0
22
0
Order By: Relevance
“…SEM analysis determined that the measure we developed has sound psychometric properties. Our results give us confidence that this new multidimensional measure of union participation provides researchers and practitioners with a robust tool for assessing and comparing the two theoretical dimensions of participation (active and passive), thereby filling an identified gap in our understanding of this construct (Gall & Fiorito, 2012a;Tripti & Ginni, 2015).…”
Section: Our Measurementioning
confidence: 62%
See 1 more Smart Citation
“…SEM analysis determined that the measure we developed has sound psychometric properties. Our results give us confidence that this new multidimensional measure of union participation provides researchers and practitioners with a robust tool for assessing and comparing the two theoretical dimensions of participation (active and passive), thereby filling an identified gap in our understanding of this construct (Gall & Fiorito, 2012a;Tripti & Ginni, 2015).…”
Section: Our Measurementioning
confidence: 62%
“…This makes the union participation construct valuable both practically (i.e., to unions and labour leaders) and academically, as it is something that unions can directly influence in a manner that will facilitate union renewal (Behrens et al, 2004;Bolton et al, 2007;Gall & Fiorito, 2012a). Unfortunately, despite the perceived importance of active union participation to union renewal (Gall & Fiorito, 2012a), a generally accepted measure of active versus passive union participation has not been developed (Tripti & Ginni, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…A survey of the union participation literature indicates that researchers have identified predictors of union participation at the individual, organizational (union), and societal levels. For example, Tripti and Ginni (2015) undertook a literature review in which they systematically categorized research on individual and organizational (union) level antecedents to union participation. Some important antecedents to participation they identified include union commitment, pro-union attitudes, union instrumentality, and union support.…”
Section: Predictors Of Union Participationmentioning
confidence: 99%
“…278). Union commitment has been found to be a primary predictor of union participation (Gall and Fiorito, 2012a;Tripti and Ginni, 2015), with those who score high in union commitment being more likely to participate in union activities than those who do not. Gordon et al (1980) observed that "since the ability of union locals to attain their goals is generally based on the members' loyalty, belief in the objectives of organized labor, and willingness to perform services voluntarily, commitment is part of the very fabric of unions" (pg.…”
Section: Predictors Of Union Participationmentioning
confidence: 99%
See 1 more Smart Citation